2010
DOI: 10.1007/s12012-010-9086-7
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Role of Fenofibrate in Preventing Nicotine- and Sodium Arsenite-Induced Vascular Endothelial Dysfunction in the Rat

Abstract: The present study investigated the effect of fenofibrate, an agonist of PPAR-alpha, in nicotine- and sodium arsenite-induced vascular endothelial dysfunction (VED) in rats. Nicotine (2 mg/kg/day, i.p., 4 weeks) and sodium arsenite (1.5 mg/kg/day, i.p., 2 weeks) were administered to produce VED in rats. The scanning electron microscopy study in thoracic aorta revealed that administration of nicotine or sodium arsenite impaired the integrity of vascular endothelium. Further, administration of nicotine or sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
(67 reference statements)
2
10
0
1
Order By: Relevance
“…On the other hand, treatment with fenofibrate significantly ameliorated the impaired renal oxidative status which is accompanied with increases in the renal levels of NO and eNOS mRNA, suggesting the renoprotective effect of fenofibrate is possibly via reversed eNOS uncoupling and improvement of endothelial function. Our results are consistent with previous studies [50,51] which reported that fenofibrate improves the integrity and function of vascular endothelium through the activation/upregulation of eNOS expression and generation of NO with a reduction in oxidative stress [50]. Previously, it has been shown that the AMPK pathway reduces intracellular ROS levels [19].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, treatment with fenofibrate significantly ameliorated the impaired renal oxidative status which is accompanied with increases in the renal levels of NO and eNOS mRNA, suggesting the renoprotective effect of fenofibrate is possibly via reversed eNOS uncoupling and improvement of endothelial function. Our results are consistent with previous studies [50,51] which reported that fenofibrate improves the integrity and function of vascular endothelium through the activation/upregulation of eNOS expression and generation of NO with a reduction in oxidative stress [50]. Previously, it has been shown that the AMPK pathway reduces intracellular ROS levels [19].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this proposal, more prolonged exposure of rats to As III (1.5 mg/kg per day for 2 weeks) attenuates ex vivo aortic relaxations to acetylcholine in association with elevated serum markers of oxidative stress (Kaur et al, 2010). Indeed, in this particular experimental model of arsenic toxicity, serum oxidant markers and impaired vessel relaxation (see Fig.…”
Section: Implies That Osupporting
confidence: 75%
“…Indeed, in this particular experimental model of arsenic toxicity, serum oxidant markers and impaired vessel relaxation (see Fig. 2) are restored by the peroxisome proliferator-activated receptor g ligands fenofibrate and roziglitazone and also by atorvastatin (Jindal et al, 2008;Kaur et al, 2010;Verma et al, 2010), agents that are associated variously with increased (6R)-5,6,7,8-tetrahydrobiopterin synthesis (through the upregulation of GTP-cyclohydrolase-I), reduced serum levels of asymmetric dimethylarginine (an endogenous NOS inhibitor), increased eNOS phosphorylation, and suppressed vascular p22 phox expression, nitrotyrosine formation, and O 2…”
Section: Implies That Omentioning
confidence: 79%
“…(53) The induction of 2 oxidative stress markers by TNF-alpha in the CMECs (p22PHOX and mitochondrial ROS levels) was prevented by fenofibrate pretreatment. Fenofibrate's antioxidant properties have previously been demonstrated in an in vivo study by reducing superoxide anion levels and p22PHOX expression in a model of nicotine-treated rat aortic tissue; (54,55) however the authors did not investigate the effects in endothelial cells. Although fenofibrate pretreatment did not alter TNF-alpha-induced activation of NF-KB in our hands, it was associated with a marked improvement in cell viability and reduced caspase-3 mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%